High specific fluorescent method staining of zinc-insulin complex in pancreatic B-cells - Meyramova, A.G.; Kohnert, K.-D.; Aitkulov, A.M.; Alina, A.R.; Zhuzbaeva, G.O.; Kystaubaeva, Z.T.; Andreewa, A.P.; Kovalenko, O.L.; Zhuzshasarova, A.A.; Tyrzhanova, S. (Изд-во КарГУ, 2013)
Authors demonstrated results using of high specific fluorescent method histochemical staining of Zn+2-ions in pancreatic B-cells. It was showed in diabetic animals and in animals past mobilization of insulin from B-cells a simultaneous decreasing as of amount of insulin as of Zn+2-ions in cytoplasm of B-cells. Meanwhile for- mation in B-cells of chemical complexes of derivatives of Diethyldithiocarbamic acid with Zn+2-ions result negative fluorescent reaction for Zn+2-ions but positive reaction for insulin using of insulin staining methods.
Keywords: insulin contents; immunohistochemical; immunofluorescent; pseudoisocyanine; aldehyde fuchsine method; pancreatic B-cells